Effects of vaginal progesterone for maintenance tocolysis on uterine electrical activity. Issue 3 (3rd January 2018) - Lucovnik, Miha; Trojner Bregar, Andreja; Bombac, Lea; Gersak, Ksenija; Garfield, Robert E.
Abstract: Aim: The effectiveness of vaginal progesterone for maintenance tocolysis after arrested preterm labor remains controversial. Myometrial contractility can be assessed objectively and non‐invasively after progesterone treatment by monitoring uterine electromyography (EMG). We examined the effects of vaginal progesterone on uterine EMG after successful acute tocolysis. Methods: This was a randomized, double‐blind, single‐center study performed between 2012 and 2015. Thirty women who experienced preterm labor between 24 0/7 and 33 6/7 weeks were randomly allocated to groups administered either 400 mg vaginal progesterone or a placebo 48 h after acute tocolysis. EMG measurements were taken prior to and 1 h and 2 h following treatment. Mann–Whitney U tests were used to compare EMG power density spectrum peak frequency and peak amplitude, propagation velocity of EMG signals, and duration and number of EMG bursts in 30 min recordings between the groups ( P  < 0.05). Results: EMG propagation velocity was higher in patients receiving the placebo compared to those treated with progesterone at 1 h (27.83 ± 10.66 vs 15.60 ± 2.94 cm/s) and 2 h (26.97 ± 13.39 vs 15.12 ± 2.58 cm/s) following treatment ( P  = 0.001). PDS peak frequencies were higher in the placebo compared to the progesterone group at 2 h following treatment (0.54 ± 0.11 vs 0.44 ± 0.06 Hz; P = 0.003). Conclusions: Treatment of 400 mg of vaginal micronized progesterone as maintenance tocolysis significantly reduces the propagation velocity of electrical signals within the myometrium and is associated with a shift toward lower uterine electrical signal frequencies.